Ganoderma Wood-Rotting Fungi on Citrus Stumps - Stephen H. Futch; James H. Graham; Larry W. Duncan; Lavern W. Timmer (EDIS, 2006)
This document is HS1019, one of a series of the Horticultural Sciences Department, UF/IFAS Extension. Original publication date March 2006.